Catalytic Reduction of 4-Nitrophenol and Methylene Blue with Silver Nanoparticles Decorated with Drymoglossum piloselloides Extract - Awalul Fatiqin; Rokiy Alfanaar; Sudarman Rahman; Yahya Febrianto; Shesanthi Citrariana; Mu’afa Purwa Arsana; Thathit Suprayogi; Yehezkiel Steven Kurniawan (Journal of Multidisciplinary Applied Natural Science, 2024)
Drymoglossum piloselloides is one of the epiphytic plants that is commonly found in Southeast Asia region. In this study, the ethanol extract of D. piloselloides plant has been used in the green synthesis of silver nanoparticles. The synthesized silver nanoparticles were characterized by ultraviolet-visible (UV-Vis) spectrophotometry, X-ray diffraction (XRD),Fourier-transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM) measurements. The UV-Vis spectrum of silver nanoparticles showed a maximum wavelength at 453 nm. The XRD measurement showed the silver nanoparticles peaks at 38.38°, 44.60°, 64.76°, and 77.62°. The FTIR spectra provided evidence of the interaction between silver and chemicals in the plant extract as a weak signal at 682 cm-1. Meanwhile, TEM revealed an average size of 12.63nm. The synthesised silver nanoparticles were utilised for the reduction of 4-nitrophenol with a conversion percentage of up to 100% with a reduction reaction rate constant of 7.104 s-1. In addition, methylene blue was also successfully reduced with the synthesised silver nanoparticles as the catalyst with a reduction reaction rate constant (k) of 21.150 s-1. This study highlights the superior advantage of utilizing ethanolic extract of D. piloselloides to prepare silver nanoparticles with promising catalytic reduction purposes.